Pseudo-Effectiveness in Regional Labor Policy: Evaluating Bureaucratic Dynamics of Job Placement Program Implementation in Klaten - Punto Bilowo; Rutiana Dwi Wahyunengseh; Rina Herlina Haryanti (Jurnal Ners, 2026)
This study evaluates the effectiveness of regional labor policy by identifying the bureaucratic factors that influence the implementation of the Job Placement Program (PTK) at the Department of Industry and Labor of Klaten Regency. In practice, however, the program has struggled to achieve its strategic goals of reducing poverty and unemployment, as high levels of administrative activity have not translated into actual job placements for program participants. Employing a case study design with a single embedded unit of analysis, the research investigates the bureaucratic "black box" using the theoretical frameworks of Grindle and Jones. Primary data were gathered through in-depth interviews with policy actors at the Department of Industry and Labor, industrial partners, and program participants, while secondary data were sourced from official strategic plans, budget documents, and standard operating procedures. The analysis follows an interactive model involving data condensation, display, and gap analysis. The findings reveal a phenomenon of pseudo-effectiveness, where the regional labor policy appears successful at an administrative level but fails to facilitate meaningful formal employment for its participants. This implementation gap is primarily driven by a misalignment between vocational training curricula and industrial needs, institutional weaknesses such as the absence of regional training centers, and procedural inefficiencies in information distribution. The study concludes that successful regional labor policy requires a more responsive bureaucratic system that aligns worker qualifications with local market demands. These results provide critical insights for regional governments to shift from procedural compliance toward substantive economic outcomes for the community.